The Use of Mycotoxin Binder to Control Its Contamination in Feed - Prima Mei Widiyanti; Romsyah Maryam (Indonesian Center for Animal Research and Development, 2016)
The climate in Indonesia as a tropical country is very condusive for the growth of mycotoxins producing fungi. Mycotoxins have properties as carcinogenic, mutagenic, teratogenic, estrogenic, neurotoxic, and immunotoxic. Mycotoxins reduce performance, appetite, weight, and immunity. They also cause reproductive disorders and generate the residues in animal products that affect human health. These can be prevented by controlling mycotoxins contamination in agricultural products that used for feed ingredients through good management practices (during planting, harvesting, and storage). Mycotoxins contamination can also be minimized by physical, chemical and biological treatments as well as the application of mycotoxin binders. This review describes the use of mycotoxin binders in animal feed. They are used as feed additives, may be derived from organic, inorganic materials or their combination. Combination of organic and inorganic substances proven to be more effective and efficient in controlling mycotoxin contamination. Therefore, it is recommended to use mycotoxin binders to prevent animal health disorder and to decrease mycotoxin residues in animal products.